2008
DOI: 10.7773/cm.v34i1.1263
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplankton fraction in the phytoplankton structure in the southern Gulf of Mexico (April 2000)

Abstract: Phytoplankton, especially the nanoplankton fraction, and its possible relationships with the hydrographic conditions in the southern Gulf of Mexico were studied during an oceanographic cruise in April 2000. Hydrographic data and phytoplankton were analyzed. Phytoplankton species composition showed heterogeneity among stations. A total of 180 species were found: 114 diatoms, 32 dinoflagellates, 32 coccolithophores, and 2 silicoflagellates. Diversity indices were variable (0.96–5.12 bits ind–1). Phytoplankton wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 27 publications
1
7
0
7
Order By: Relevance
“…Few studies have been conducted on the planktonic communities of Campeche Canyon. Hernández-Becerril et al (2008) observed a predominance of the coccolithophore Emiliania huxleyi and the diatom Nitzschia bifurcata. In summer, most of the zooplankton biomass occurs below the thermocline, in the upper 60 m layer (Mojica-Ramírez 2003).…”
Section: áRea De Estudiomentioning
confidence: 94%
See 1 more Smart Citation
“…Few studies have been conducted on the planktonic communities of Campeche Canyon. Hernández-Becerril et al (2008) observed a predominance of the coccolithophore Emiliania huxleyi and the diatom Nitzschia bifurcata. In summer, most of the zooplankton biomass occurs below the thermocline, in the upper 60 m layer (Mojica-Ramírez 2003).…”
Section: áRea De Estudiomentioning
confidence: 94%
“…Existen pocos estudios concernientes a las comunidades planctónicas sobre el Cañón de Campeche. Hernández-Becerril et al (2008) encontraron una predominancia del cocolitofórido Emiliania huxleyi y de la diatomea Nitzschia bifurcata. En verano la mayor cantidad de biomasa zooplanctónica se encuentra debajo de la termoclina, en la capa superior de 60 m de profundidad (Mojica-Ramírez 2003), mientras que en invierno, durante la temporada de tormentas invernales localmente conocidas como "Nortes", las comunidades de zooplancton estuvieron dominadas por copépodos y la mayor abundancia de zooplancton se encuentra en torno a la termoclina, esto como resultado del incremento del espesor de la capa de mezcla (Ramírez-Cruz 2005).…”
Section: Hydrographic Data and Phytoplankton Samples Includingunclassified
“…Studies from the southern and southwestern GoM have also been conducted on various ecological aspects of phytoplankton and primary productivity (e.g. Okolodkov, 2003;Hernández-Becerril et al, 2008). Many of these studies have traditionally considered the microplankton fraction, especially large diatoms and dinoflagellates, as the main contributors to primary production (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies have traditionally considered the microplankton fraction, especially large diatoms and dinoflagellates, as the main contributors to primary production (e.g. Hernández-Becerril & Flores, 1998;Licea et al 2004, Hernández-Becerril et al, 2008.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation